Case report: Genotype-phenotype characteristics of nine novel PKD1 mutations in eight Chinese patients with autosomal dominant polycystic kidney disease - Zhuang, Jing; Aierken, Ailima; Yalikun, Dilina; Zhang, Jun; Wang, Xiaoqin; Ren, Yongfang; Tian, Xuefei; Jiang, Hong (Frontiers in Medicine, 2023)
Introduction: Autosomal dominant polycystic kidney disease (ADPKD) is a common genetic disorder. The PKD1 gene is responsible for the majority of ADPKD cases, and the mutations in this gene exhibit high genetic diversity. This study aimed to investigate the association between genotype and phenotype in ADPKD patients with PKD1 gene mutations through pedigree analysis.Methods: Eight Chinese pedigrees affected by ADPKD were analyzed using whole-exome sequencing (WES) on peripheral blood DNA. The identified variants were validated using Sanger sequencing, and clinical data from the patients and their families were collected and analyzed.Results: Nine novel mutation sites in PKD1 were discovered across the pedigrees, including c.4247T>G, c.3298_3301delGAGT, c.4798A>G, c.7567G>A, c.11717G>C, c.7703+5G>C, c.3296G>A, c.8515_8516insG, and c.5524C>A. These mutations were found to be associated with a range of clinical phenotypes, including chronic kidney disease, hypertension, and polycystic liver. The age of onset and disease progression displayed significant heterogeneity among the pedigrees, with some individuals exhibiting early onset and rapid disease progression, while others remained asymptomatic or had milder disease symptoms. Inheritance patterns supported autosomal dominant inheritance, as affected individuals inherited the mutations from affected parents. However, there were instances of individuals carrying the mutations who remained asymptomatic or exhibited milder disease phenotypes.This study highlights the importance of comprehensive genotype analysis in understanding the progression and prognosis of ADPKD. The identification of novel mutation sites expands our knowledge of PKD1 gene mutations. These findings contribute to a better understanding of the disease and may have implications for personalized therapeutic strategies.